Shirley Chisholm, Catalyst for Change: A Portrait in Eight Parts - Ghodsi, Yasaman. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Music.; Advisor: Kareem Roustom.; Committee: Jennifer Burton, and John McDonald.; Keywords: Musical composition, and Music.